2021
DOI: 10.5187/jast.2021.e63
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of causative agents of calf diarrhea in Korean native calves

Abstract: Infectious calf diarrhea is one of the most significant diseases of neonatal calves. This study is conducted to identify the prevalence of pathogens in calf diarrhea for 2 years. A total of 544 feces samples from Korean native beef calves were obtained to investigate selected seven pathogens causing calf diarrhea: bovine rotavirus, bovine coronavirus, Cryptosporidium parvum, bovine viral diarrhea virus, Eimeria species, Escherichia coli K99, and Salmonella species. The presence of diarrhea, the number and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Calf (G1-1) in the G1 group had BCoV RNA in its feces, with a ct value of 37.6-38.1, whereas calf G1-2 had a ct value of 36.2-37.5. However, a previous paper that performed RT-PCR using the primers and probes used in the present study defined a positive RT-PCR ct value < 35 [28]. Therefore, in the pathogenicity reversal experiment using the KBR-1-p120 strain, the ct values detected in samples from calves in the G1 group were almost negative.…”
Section: G1mentioning
confidence: 51%
“…Calf (G1-1) in the G1 group had BCoV RNA in its feces, with a ct value of 37.6-38.1, whereas calf G1-2 had a ct value of 36.2-37.5. However, a previous paper that performed RT-PCR using the primers and probes used in the present study defined a positive RT-PCR ct value < 35 [28]. Therefore, in the pathogenicity reversal experiment using the KBR-1-p120 strain, the ct values detected in samples from calves in the G1 group were almost negative.…”
Section: G1mentioning
confidence: 51%
“…Fecal samples were previously tested for the presence of common diarrhea-causing pathogens, such as Escherichia coli K99, Salmonella spp., Cryptosporidium spp., bovine coronavirus, bovine rotavirus, and bovine viral diarrhea virus and all pathogens except Salmonella spp. were detected in feces (1).…”
Section: Resultsmentioning
confidence: 98%
“…A previous study of BoRVA-positive Korean native calves reported that 17.1% (28/164) of diarrhea samples were obtained in Gangwon and Gyeongbuk provinces between 2014 and 2016 from calves aged less than 7 months [ 5 ]. Another study of fecal samples collected in 2016–2017 from Korean calves aged up to 60 days showed that the BoRVA-positive rate for diarrhea feces was 15.2% (31/204), compared with 5.0% (17/340) for normal feces [ 6 ]. In addition, we found a BoRVA-positive rate of 25.4%, with the prevalence being above this average in four regions (Chungnam, Gyeongbuk, Gyeonggi, and Jeonbuk).…”
Section: Discussionmentioning
confidence: 99%
“…Although not much research has been done to date, bovine coronaviruses, bovine viral diarrhea viruses, and RVs have been identified as important diarrhea-causing viruses prevalent in Korean calves [ 5 , 6 , 7 , 8 , 9 , 10 ]. Among these various diarrhea-causing pathogens, bovine rotavirus (BoRVA) is the primary causative agent in calves aged less than one month [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%